2018
DOI: 10.3390/su10124555
|View full text |Cite
|
Sign up to set email alerts
|

Application of Traditional Knowledge of Hani People in Biodiversity Conservation

Abstract: Traditional knowledge offers a feasible approach to biodiversity conservation because it not only preserves, but also enriches biodiversity [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The diversity of landraces can ensure farmers to cope with the challenge of environmental uncertainty, provide genetic materials for modern breeding work, enlarge the genetic basis of parental materials and meet the needs of the adaptation and evolution under the condition of global warming and changing production conditions (Lopes et al, 2015;Jarvis et al, 2016). Due to the special and complex ecological environment and the needs of local traditional culture and habits, most ethnics who live in the mountains of southwest China prefer to grow various landraces, which makes the rich resources of landraces retained (Zeng et al, 2001;Zhang et al, 2007;Yang et al, 2018). It was reported that there were 76 upland landraces cultivated by Jinuo people and 61 highland barley landraces in the Tibetan area of northwest Yunnan have been reserved (Li et al, 2011).…”
Section: Highlightsmentioning
confidence: 99%
“…The diversity of landraces can ensure farmers to cope with the challenge of environmental uncertainty, provide genetic materials for modern breeding work, enlarge the genetic basis of parental materials and meet the needs of the adaptation and evolution under the condition of global warming and changing production conditions (Lopes et al, 2015;Jarvis et al, 2016). Due to the special and complex ecological environment and the needs of local traditional culture and habits, most ethnics who live in the mountains of southwest China prefer to grow various landraces, which makes the rich resources of landraces retained (Zeng et al, 2001;Zhang et al, 2007;Yang et al, 2018). It was reported that there were 76 upland landraces cultivated by Jinuo people and 61 highland barley landraces in the Tibetan area of northwest Yunnan have been reserved (Li et al, 2011).…”
Section: Highlightsmentioning
confidence: 99%
“…With unique natural ecological landscape, they provide effective resources for regional sustainable development and have attracted extensive attention of human beings. The Hani people are mainly distributed in Yunnan Province, China, and are an ancient ethnic minority in China with a long history and unique culture [1]. During mankind's long history of interactions with nature [2], the Hani people have formed traditional ethnic villages, which reflect their ethnic characteristics, historical culture, farming civilization, and folk customs.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, typical traditional ethnic Hani villages were selected to analyze their impact in the Hani area on sustainable development, and the MCR model was used to integrate dynamics of land use, landscape pattern, ESV, GDP, and population in a sustainability assessment. This study aims to: (1) Analyze changes in sustainability indicators within 2 km and 4 km buffer zones around traditional ethnic villages; (2) Assess the sustainability of traditional ethnic Hani villages and their impact in typical Hani areas in China from 1995-2020. This paper revealed the spatial and temporal dynamics of sustainability in the Hani area and traditional ethnic villages analyzed the causes for changes in sustainability, filled in the deficiencies of the current evaluation of sustainability in the Hani area, and provided suggestions for land use management planning and sustainable development.…”
Section: Introductionmentioning
confidence: 99%
“…Homegardens are especially important in the context of the rural areas and the regions inhabited by the tribal population where they play an important role in livelihood sustenance (Barbhuiya et al, 2016). Lots of recent studies have emphasized the importance of the IKS of various tribal communities around the world (especially those residing adjacent to the forests) as an important potential tool for biodiversity conservation, both in homegardens and the local forest, as the tribal communities around the world are known to harbour huge IKS on the use of various floras in the forest (Gadgil, 1987;Gadgil et al, 1993;Berkes, 2000;Das & Das, 2005;Parrotta & Agnoletti, 2007;Galluzi et al, 2010;Fraser et al, 2010;Kumar & Tiwari, 2017;Idohou et al, 2014;Yang et al, 2018). They have been known to domesticate many wild species of the floras in their homegardens and other agroforestry lands as a part of their livelihood security and cultural practices.…”
Section: Introductionmentioning
confidence: 99%